2023
DOI: 10.1002/wer.10896
|View full text |Cite
|
Sign up to set email alerts
|

Performance of cocultivation of Chlorella vulgaris and four different fungi in biogas slurry purification and biogas upgrading by induction of strigolactone (GR24) and endophytic bacteria

Abstract: This study aimed to determine the best fungi to form the algal-bacterial-fungal symbionts and identify the optimal conditions for the synchronous processing of biogas slurry and biogas. Chlorella vulgaris (C. vulgaris) and endophytic bacteria (S395-2) isolated from it, and four different fungi (Ganoderma lucidum, Pleurotus ostreatus, Pleurotus geesteranus, and Pleurotus corucopiae) were used to form different symbiotic systems. Four different concentrations of GR24 were added to systems to examine the growth c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Previous studies demonstrated the effects of the strigolactones analog GR24 [64,66,119] and of a natural strigolactone, 5-deoxystrigol [63], i.e., molecules that include A, B, C, and D rings, on microalgae,. The present study demonstrates, for the first time to the best of our knowledge, that strigolactone mimics, retaining only the butenolide D ring, are also active on microalgae.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated the effects of the strigolactones analog GR24 [64,66,119] and of a natural strigolactone, 5-deoxystrigol [63], i.e., molecules that include A, B, C, and D rings, on microalgae,. The present study demonstrates, for the first time to the best of our knowledge, that strigolactone mimics, retaining only the butenolide D ring, are also active on microalgae.…”
Section: Discussionmentioning
confidence: 99%